Advancing swimming through big data - Lehari, T. (FINA Golden Coaches Clinic 2016, 2016)
Mr. Tristan Lehari, Founder, Tritonwear talks about "Advancing swimming through big data" at the FINA Golden Coaches Clinic 2016 (17:19 min).